2011
DOI: 10.1007/s00394-011-0217-0
|View full text |Cite
|
Sign up to set email alerts
|

S-allylmercaptocysteine reduces carbon tetrachloride-induced hepatic oxidative stress and necroinflammation via nuclear factor kappa B-dependent pathways in mice

Abstract: PurposeTo study the protective effects and underlying molecular mechanisms of SAMC on carbon tetrachloride (CCl4)-induced acute hepatotoxicity in the mouse model.MethodsMice were intraperitoneally injected with CCl4 (50 μl/kg; single dose) to induce acute hepatotoxicity with or without a 2-h pre-treatment of SAMC intraperitoneal injection (200 mg/kg; single dose). After 8 h, the blood serum and liver samples of mice were collected and subjected to measurements of histological and molecular parameters of hepato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…Several studies suggested that CYP2E1 was degraded during CCl 4 -induced hepatotoxicity [28,29]. Our results showed that the CCl 4 -mediated reduction in CYP2E1 expression was significantly ameliorated by myricitrin, suggesting the suppression of CYP-mediated CCl 4 bioactivation.…”
Section: Discussionsupporting
confidence: 42%
“…Several studies suggested that CYP2E1 was degraded during CCl 4 -induced hepatotoxicity [28,29]. Our results showed that the CCl 4 -mediated reduction in CYP2E1 expression was significantly ameliorated by myricitrin, suggesting the suppression of CYP-mediated CCl 4 bioactivation.…”
Section: Discussionsupporting
confidence: 42%
“…The development of NAFLD in rats, including the recipe and preparation protocols of diet, was performed based on our previously described voluntary oral feeding NAFLD animal model [18]. The optimum dosage of SAMC was previously shown to be effective in protecting the liver from both acute and chronic injury [19, 20]. Instead of oral administration in a dietary supplement form, SAMC was intraperitoneally injected to avoid possible degradation prior to absorption through the gastrointestinal tract (GIT).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, SAMC also plays a preventive role in an acetaminophen-induced acute liver injury model through the inhibition of the activity of cytochrome P450 2E1 (CYP2E1) [18]. We previously demonstrated the protective properties of SAMC in both carbon tetrachloride-induced acute liver injury model [19] and NAFLD-induced chronic liver injury model [20]. In these studies, SAMC reduces the key events that contribute to the hepatic damage including oxidative stress, inflammation, and necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, SAMC is also shown to play antioxidative and anti-nitrosative stress roles both in vitro and in vivo [8]. The hepato-protective effect of SAMC is exhibited in an acetaminophen-induced liver injury model and a carbon tetrachloride-induced acute injury model where SAMC inhibits the activity of cytochrome P450 2E1 (CYP2E1) and reduces oxidative stress released by chemical intoxication [911]. However, the protective effects and underlying mechanisms of SAMC in NAFLD remain unknown.…”
Section: Introductionmentioning
confidence: 99%